Sufism and the Future of Religion: A Reflection - Faiz Ahmad Nugroho (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
Various Muslim scholars say that Sufism as "something by which we know the good and the bad of the soul, how to cleanse it of the blameworthy and fill it with commendable qualities, how to carry out mysticism and the journey to the pleasure of Allah and leave the prohibitions". Sufism among Muslims is seen as an element of the depth of religion in Islam which has the basic potential to restore the function of religion as a role model, the morals exemplified by the Prophet Muhammad SAW. Teachings about Love, longing, a relationship with the Creator that makes humans feel close, and overcomes excessive love for the world. This article explains that Sufism is able to encourage humans to be fair to others and the environment as God teaches and wills. In this regard, Islam with a style that is dominated by Sufism or Mysticism is what preachers brought to the archipelago since tens of centuries ago, and because of that, as historians have noted, the Islamization of the archipelago in general took place peacefully, through trade, and not by military expansion